Joko Widodo’s speeches at the 42nd ASEAN Summit: A critical discourse analysis - Rahmasari, Shafira; Roselani, Ni Gusti Ayu (Universitas Dian Nuswantoro, 2024)
The 42nd ASEAN Summit was held in Indonesia, making Indonesia the chairman of the Summit. Joko Widodo, as the president, represented the country to welcome the ASEAN members and open the summit and the meetings by giving remarks and statements. This study attempted to examine how interpersonal metafunction is used in the opening remarks and press statements as well as to reveal the power strategy and ideology depicted in the opening remarks and press statements. Eight opening remarks and two press statements were analyzed utilizing Halliday’s Systemic Functional Linguistics. Fairclough’s Critical Discourse Analysis was employed to reveal the power relations and the ideology. The study found declarative, interrogative, and imperative were the mood types in which it utilized probability, obligation, and inclination modality. It showed that Joko Widodo acted as the initiator to promote collaboration to achieve ASEAN’s goals.